Thematic Cluster Analysis of Online Environmental Activism from 2013 to 2025 - Loso Judijanto (The Eastasouth Journal of Social Science and Humanities, 2026)
The accelerated development of digital media has led to a paradigm shift in environmental activism, moving from offline mobilization efforts to digital media engagement. The objective of this study is to investigate the thematic development of online environmental activism from 2013 to 2025 using a thematic cluster analysis approach. By employing bibliometric methods and keyword co-occurrence analysis, this research study identifies the major themes, determines the structural relationships between research topics, and analyzes the temporal trends in the research landscape. The results show that social media and activism serve as major hubs that connect sustainability discourse, digital communication, and civic engagement. The network visualization shows a strongly interconnected thematic structure, while the overlay analysis shows a transition from the early days of internet-based activism to the current themes of sustainability governance, environmental communication, and digital citizenship. The density visualization also emphasizes the focus of research on digitally mediated activism, suggesting continuity in the fundamental research interests, as well as the development of new interdisciplinary research perspectives. This research study adds to the body of knowledge on the development of environmental activism in digital environments and offers insights into future research directions on participatory governance, communication, and digitally facilitated environmental activism.